Reducing Incarceration Rates in Australia Through Primary, Secondary, and Tertiary Crime Prevention - Battams, Samantha (Criminal justice policy review, 2021)
In Australia, incarceration rates have steadily increased since the 1980s, providing an imperative for crime prevention. We explored the extent to which Australian justice sector policies were aimed at preventing crime, using a framework for “primary, secondary and tertiary” crime prevention. We analyzed policies and legislation (n = 141) across Australian jurisdictions (a census was undertaken from May to September 2016, with policies spanning from 1900 to 2022). We found a strong focus on tertiary crime prevention, with recidivism rather than root causes of crime problematised. We also found little focus on primary crime prevention, despite some high-level cross sectoral strategies designed to prevent crime. In this paper, we will use the framework of Bacchi’s “what’s the problem?” approach, considering levels of crime prevention, social determinants of health, and discourses surrounding crime. We discuss policy implications and make suggestions for policy reform and accountability mechanisms to reduce crime and incarceration.